Mormon Envoy : The Diplomatic Legacy of Dr. John Milton Bernhisel - Worthen, Bruce (Book collections on Project MUSE., 2023)
"For more than twenty years, John Milton Bernhisel negotiated with powerful interests, including the federal government, on behalf of the Church of Jesus Christ of Latter-day Saints. Bruce W. Worthen illuminates the life and work of the man whose diplomacy steered the Church's relationship with Washington, D.C. from its early period of dangerous conflict to a peaceful and pragmatic coexistence. Having risen from a Pennsylvania backcountry upbringing to become a respected member of the upper class, Bernhisel possessed a personal history that allowed him to reach common ground with politicians and other outsiders. He negotiated for Joseph Smith's life and, after the Church's relocation to the Utah Territory, took on the task of rehabilitating the public image of the Latter-day Saints. Brigham Young's defiance of the government undermined Bernhisel's work, but their close if sometimes turbulent relationship ultimately allowed Bernhisel to make peace with Washington, secure a presidential pardon for Young, and put Utah and the Latter-day Saints on the road to formally joining the United States"--